O desenvolvimento moral e o valor respeito na educação infantil - Miguel, Priscila Caroline (Editora Oficina Universitária, 2021)
The theme of this book is the search for strategies for strengthening decentralization, overcoming egocentrism and forwarding a reversible perspective in decision-making. The main objective is the creation of a didactic sequence that works on moral development, specifically adherence to the value of respect in a reversible way, that is, working on overcoming egocentrism and recognizing the other, which is only possible with reversibility. As a result, in addition to defining the theoretical assumptions that involve the discussion of moral development and, in particular, the value of respect, we constructed a Didactic Sequence to be applied with children aged five years, seeking the moral development that implies overcoming of egocentrism and self-awareness, since egocentrism would be precisely the lack of such awareness. We believe that working with socio-moral values can help in this process and we chose the value of respect, since unilateral respect is the first form of respect that appears in the moral development of human beings and arises in social coercive relationships, in particular, those built between the child and her parents or other significant adults. On the other hand, mutual respect arises from cooperation that imposes only the reciprocity that obliges each one to put himself in the other's shoes.